2002
DOI: 10.1128/mcb.22.24.8552-8561.2002
|View full text |Cite
|
Sign up to set email alerts
|

An ATR- and Chk1-Dependent S Checkpoint Inhibits Replicon Initiation following UVC-Induced DNA Damage

Abstract: Inhibition of replicon initiation is a stereotypic DNA damage response mediated through S checkpointmechanisms not yet fully understood. Studies were undertaken to elucidate the function of checkpoint proteins in the inhibition of replicon initiation following irradiation with 254 nm UV light (UVC) of diploid human fibroblasts immortalized by the ectopic expression of telomerase. Velocity sedimentation analysis of nascent DNA molecules revealed a 50% inhibition of replicon initiation when normal human fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
236
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(257 citation statements)
references
References 62 publications
17
236
1
3
Order By: Relevance
“…Therefore, the lowdose specificity and p53 dependency of the suppression of replication fork progression may well have been overlooked. In fact, 1.5 Gy gamma-radiation was reported to induce suppression of replication fork progression in p53 proficient normal human fibroblasts (Heffernan et al, 2002). Furthermore, (Painter and Young, 1980) found radiation-induced suppression of chain elongation in p53 proficient E-11 normal human diploid cells whereas the same authors found no such suppression in p53 mutated cell line as discussed above (Painter and Young, 1975).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the lowdose specificity and p53 dependency of the suppression of replication fork progression may well have been overlooked. In fact, 1.5 Gy gamma-radiation was reported to induce suppression of replication fork progression in p53 proficient normal human fibroblasts (Heffernan et al, 2002). Furthermore, (Painter and Young, 1980) found radiation-induced suppression of chain elongation in p53 proficient E-11 normal human diploid cells whereas the same authors found no such suppression in p53 mutated cell line as discussed above (Painter and Young, 1975).…”
Section: Discussionmentioning
confidence: 94%
“…The original mutant fibroblast strains were obtained from the NIGMS Human Genetic Cell Repository (GM02052A, AT) and the American Type Culture Collection (CRL1162, XP-V, strain XP4BE). Immortalized cell lines from these strains of human fibroblasts were obtained by ectopic expression of human telomerase (hTERT), as previously described [25]. The derivative cell lines described below are also immortalized.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…These were performed essentially as described [25]. Briefly, logarithmically growing cells were seeded at 10 6 per 100 mm dish and incubated for 40 h. Cultures were treated as specified in the figure legends, harvested by trypsinization, washed once in PBS, and resuspended in lysis buffer (10 mM sodium phosphate buffer, pH 7.2, 1 mM EDTA, 1 mM EGTA, 150 mM NaCl, 1% NP40, supplemented with 10 mM 4-(2-aminoethyl) benzenesulfonyl fluoride (AEBSF), 10 mM β-glycerophosphate, 10 mM sodium orthovanadate, and 10 μg/ml of leupeptin and aprotinin).…”
Section: Western-blot Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The human cells used in these studies were NHF1-hTERT, a cell line derived from normal neonatal foreskin fibroblasts (Boyer et al, 1991) and immortalized by ectopic expression of the catalytic subunit of telomerase (Heffernan et al, 2002); GM1604-hTERT, a male fetal lung fibroblast cell line also immortalized by telomerase expression (Ouellette et al, 2000); and CRL-1502 cells (ATCC), a strain of female fetal lung fibroblasts. The hTERT-immortalized cell lines were grown in minimal essential medium (Invitrogen, Carlsbad, CA) containing 2X the concentration of MEM non-essential amino acids (Invitrogen).…”
Section: Cell Culturesmentioning
confidence: 99%